The effect of risk on profitability in banks listed on the Indonesia Stock Exchange - Shofiati Irbah Shofiati Irba; Dina Patrisia (Universitas Negeri Padang, 2021)
This study aims to analyze the effect of (1) insolvency risk, (2) liquidity risk, (3) credit risk, (4) security risk, (5) capital risk, (6) market risk, and (7) operational risk on profitability in banks listed on the Indonesia Stock Exchange. The population in this study were all 50 banks listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique in this study used the purposive sampling technique with a total sample of 30 banks from 2015-2019. The data used in this study is secondary data obtained from www.idx.co.id with multiple regression analysis as the analysis tool. The results of this study indicate that (1) insolvency risk has a positive and significant effect on the profitability of banks that have Go Public, (2) liquidity risk has a positive and insignificant effect on profitability of banks that have Go Public,